Long-Term Follow-Up of Autonomic and Enteric Measures in Patients Undergoing Vertical Banded Gastroplasty for Morbid Obesity - Crittenden, Neil E. (Gastroenterology Res, 2017)
BACKGROUND: A multi-component model of autonomic and enteric factors may correlate with ultimate weight loss or gain after restrictive obesity surgery. This study aimed to determine relevant parameters to predict successful long-term weight loss. METHODS: Thirty-nine patients (four males and 35 females) with a mean age of 37.2 years were followed for over 15 years after vertical banded gastroplasty. Baseline adrenergic: postural adjustment ratio (PAR) and vasoconstriction (VC); cholinergic: electrocardiogram R-to-R interval (RRI) and enteric measure: electrogastrogram (EGG) were utilized by a discriminant function analysis to classify patients as a long-term loser or gainer. Using latest weight compared to baseline, patients were divided as 10 gainers and 29 losers. RESULTS: A discriminate model successfully predicted ultimate weight gain in 8/10 (80%) of patients who subsequently gained weight and weight loss in 24/29 (83%) of patients who lost weight for a total correct classification of 32/39 (82%). The same model with data at 3 months postoperatively predicted weight gain in 9/10 (90%) of patients and weight loss in 24/29 (83%) of patients, for a total correct classification of 34/39 (87%). CONCLUSIONS: A multi-component model at baseline and 3 months postoperative can predict long-term weight outcome from restrictive obesity surgery.